Mercury in Dried Market Fish of Hong Kong and San Francisco: Human Health Implications - Vallentyne, Dan; Zhao, Ziyang; Yung Lee, Tak; McGuire, David (Journal of Asian Health, 2022)
Asian, Asian Pacific Islanders, and Asian American residents of San Francisco have higher exposure to mercury and the associated health risks associated with methylmercury toxicity from fish consumption than other demographics across the United States. Due to their higher annual fish consumption, Hong Kong Chinese residents have elevated risks to methylmercury exposure. Objectives: We investigate samples of dried market fish from San Francisco and from Hong Kong as potential sources of mercury contamination in fish commonly consumed by Asian and Asian American residents. Methods: We analyze 81 samples of dried market fish from San Francisco and Hong Kong for mercury concentration using Inductively Coupled Plasma Emission Spectrograph and Processing Cold Vapor Atomic Fluorescence Spectrometry. We binned into market categories, trophic level, and habitat type for statistical analysis. Results: No significant difference was observed in the mercury levels of samples between San Francisco and Hong Kong (p-value = 0.47). Dried samples did show higher rates of mercury than wet samples reported by the FDA. Data from dried market fish samples also show evidence of bioaccumulation: the concentration of toxins in higher trophic levels of fish (p-value < 0.01). Eliminating apex predators, nearly all samples of fish from both locations and from lower trophic levels had levels below the lowest health advisory thresholds of 0.5 ppm methylmercury by weight. Discussion: Dried fish samples from markets in San Francisco and Hong Kong showed mercury levels with the potential to exceed guidelines set by the EPA and the EFSA, but consumption rates are lacking to know if this threshold is actually being exceeded by consumers. We make recommendations regarding the health risks of dried market fish and of consuming or avoiding fish from certain trophic groups.